On coupled oscillator dynamics and incident behaviour patterns in slime mould Physarum polycephalum: emergence of wave packets, global streaming clock frequencies and anticipation of periodic stimuli. Issue 1 (2nd January 2017) - Mayne, Richard; Jones, Jeff; Gale, Ella; Adamatzky, Andrew
Abstract : Slime mould Physarum polycephalum is a single cell which physically oscillates via contraction of actomyosin in order to achieve motility. Several of its apparently 'intelligent' behaviour patterns such as anticipatory responses to periodic stimuli have recently been attributed as functions of the coupling between the oscillating intracellular reactions which drive its rhythmic muscular contraction, but the mechanisms that underlie these phenomena have not yet been experimentally verified. Through laboratory investigations in which we entrain the P. polycephalum plasmodium via periodic ultraviolet light exposure we find that this phenomenon is likely to result from biasing its various oscillating life processes through altering local concentration profiles of various allosteric molecules and their effectors. This temporarily overwrites the global streaming clock frequency and eradicates the wave packets usually observed in slime mould biomechanical oscillation. This response is likened to an intracellular chemical memory. We proceed to present a multi-agent model in which we demonstrate that travelling waves and oscillatory clock frequencies may emerge in the virtual organism's biomechanical oscillator, although anticipatory responses cannot be replicated by simple mechanical interactions. We conclude by arguing that these phenomena are best characterised as analogue computation and discuss practical applications therein. Graphical Abstract: The Physarum polycephalum actin network in a plasmodial tubule. SiR-actin staining, scale bar 200 μm.